Relationship Between Stressful Life Events And Anxiety During The Period Of Adolescence - Stankovska, Gordana; Osmani, Fadbi; Grncarovska, Svetlana Pandilovska; Angelkoska, Slagana (European Scientific Journal, ESJ, 2016)
The purpose of this study is to investigate the relationships between stressful life events and anxiety during the period of adolescence. It is known that stressful life events are commonly studied risk and environmental factors in the development of psychopathology in childhood and adolescence. In addition, physical and psychological symptoms of anxiety are often associated with stressful life events. These events are related to the different experiences of conflict and disrupted communication in the family. Subsequently, these events directly or indirectly affect the self-esteem and the self-image of adolescents during the period of adolescence. This research starts with the assumption that stressful life events predicted anxiety during the period of adolescence. Another assumption, in this research, is that females have higher level of anxiety compared with males. This study was conducted on a sample of 160 participants (80 girls and 80 boys) students in the fourth year of secondary school. The instruments used in the research include: scale of stressful life events for children and adolescents – Stress-D, and the Scale for anxiety for children and adolescents – SCAD-62. The results showed that stressful life events were significantly associated with anxiety symptoms (r= .962, p<.01). Also, the symptoms of anxiety are closely associated with medical (F,24,135= .871, p<.05) and family stressful events (F,24,135= 2.017, p<.05). There were significant relationship between medical stressful life events and gender (p= .045), and social stressful life events and gender (p= .001). On the other hand, there was a negative correlation between academic stressful life events and gender (p= .944), and family stressful life events and gender (p= .564). In conclusion, the results of the study show that females have higher level of anxiety compared with males (r= .985, p<.01). The results show that there is a significant relationship between specific types of stressful life events, including those related to physical health and family which discord the anxiety during the period of adolescence.